Prospective use of collected fog water in the restoration of degraded burned areas under dry Mediterranean conditions (Agricultural and Forest Meteorology, 2009)
A mountainous plot located in the interior of the Valencia region (east coast of the Iberian Peninsula) was identiﬁed for reforestation using the fog-water collection potential prevailing in the area. Fog data were obtained by means of an instrument ensemble consisting of a passive cylindrical fog-water collector, a rain gauge, a wind direction and velocity sensor and a temperature and humidity probe. Preliminary results gave rise to the additional deployment of a low-cost 18-m2 ﬂat-panel collector connected to three 1000-l tanks for larger scale fog-water collection and storage. The 2007 annual rate of fog water that could be derived from the instrument ensemble amounted to 3.3 l/m2 /day, which turn out to ﬁll up the storage tanks completely in only 5 months, even though the ﬂat-panel collector could not be operative 100% of the time. The study made use of the in situ stored water and a micro-irrigation network to irrigate a plot of reforestation seedlings through small water pulses localized deep in the planting hole during the summer dry period. Until the present, this forest location had always shown a difﬁcult self-recovery due to the high level of land degradation resulting from recurrent forest ﬁres in the past. Results indicate that survival rates and seedling performance of the two species planted, Pinus pinaster and Quercus ilex, improved with the use of small timely waterings and additional treatments with composted biosolid.